The use of breastfeeding pillow to reduce discomfort for breastfeeding mothers - Ida Ayu Kade Sri Widiastuti; Yeni Rustina; Defi Efendi (MDPI AG, 2020)
The process of breastfeeding for newborns in the special care room often experiences obstacles due to diverse factors, such as environmental factors, hospitalization impact, and maternal discomfort during breastfeeding. The aim of this study was to determine whether breastfeeding pillows decrease maternal discomfort during breastfeeding. This research employed a randomized control trial (RCT) design involving 70 participants who were divided into an intervention (n=35) and a control group (n=35) based on the inclusion criteria. The intervention group used a breastfeeding pillow while breastfeeding the baby, and the control group provided ASI (breast milk) as recommended in the treatment room. The data measurement instruments were an observation sheet and the body part discomfort scale (BPDS). The BPDS comprised 4 assessments: the initial assessment, day I assessment, day II assessment, and the final assessment. The results of the GLM-RM analysis showed a significant reduction in maternal discomfort among participants using breastfeeding pillows (P<0.05). Supporting facilities such as breastfeeding pillows are needed to improve maternal comfort to increase the breastfeeding period and ensure optimal nutrition.